Parathyroid hormone increases alveolar bone homoeostasis during orthodontic tooth movement in rats with periodontitis via crosstalk between STAT3 and β-catenin - Cheng Zhang; Tiancheng Li; Chenchen Zhou; Li Huang; Yuyu Li; Han Wang; Peipei Duan; Shujuan Zou; Li Mei (Nature Publishing Group, 2020)
Abstract Periodontitis patients are at risk of alveolar bone loss during orthodontic treatment. The aim of this study was to investigate whether intermittent parathyroid hormone (1-34) treatment (iPTH) could reduce alveolar bone loss during orthodontic tooth movement (OTM) in individuals with periodontitis and the underlying mechanism. A rat model of OTM in the context of periodontitis was established and alveolar bone loss was observed. The control, iPTH and iPTH + stattic groups received injections of vehicle, PTH and vehicle, or PTH and the signal transducer and activator of transcription 3 (STAT3) inhibitor stattic, respectively. iPTH prevented alveolar bone loss by enhancing osteogenesis and suppressing bone resorption in the alveolar bone during OTM in rats with periodontitis. This effect of iPTH was along with STAT3 activation and reduced by a local injection of stattic. iPTH promoted osteoblastic differentiation and might further regulate the Wnt/β-catenin pathway in a STAT3-dependent manner. The findings of this study suggest that iPTH might reduce alveolar bone loss during OTM in rats with periodontitis through STAT3/β-catenin crosstalk.